93.1k views
3 votes
Solve (2x-10)=(65-x) show your work plz!

User Huafu
by
5.3k points

2 Answers

2 votes
^ they showed the work Give me thanks and the answer is x=25
User George Host
by
5.4k points
6 votes

Answer: x=25

Explanation:

Simplifying

(2x + -10) = (65 + -1x)

Reorder the terms:

(-10 + 2x) = (65 + -1x)

Remove parenthesis around (-10 + 2x)

-10 + 2x = (65 + -1x)

Remove parenthesis around (65 + -1x)

-10 + 2x = 65 + -1x

Solving

-10 + 2x = 65 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.

-10 + 2x + x = 65 + -1x + x

Combine like terms: 2x + x = 3x

-10 + 3x = 65 + -1x + x

Combine like terms: -1x + x = 0

-10 + 3x = 65 + 0

-10 + 3x = 65

Add '10' to each side of the equation.

-10 + 10 + 3x = 65 + 10

Combine like terms: -10 + 10 = 0

0 + 3x = 65 + 10

3x = 65 + 10

Combine like terms: 65 + 10 = 75

3x = 75

Divide each side by '3'.

x = 25

Simplifying

x = 25

Sorry if its too confusing!

User NetByMatt
by
5.1k points